Competitive coordination of iron(III) and copper(II) ions with amidoximated polyacrylonitrile nanofiber and the catalytic performance of the complex. Issue 1 (June 2022) - Li, Fu; Fei, Pengfei; Dong, Yongchun; Zhang, Man; Feng, Yu; Liu, Shuqiang; Jia, Lu
This present work describes the competitive coordination of iron (III) and copper (II) ions with amidoximated polyacrylonitrile nanofiber and the catalytic performance of the resulting complex (Fe-Cu-AO- n -PAN). The coordination results showed that the increase of the initial concentration of metal ions was beneficial to the increase of the coordination amount. There were both competition and synergistic effects between the two metal ions. But AO- n -PAN was more inclined to coordinate with Fe 3+ ions. The promotion effect of Cu 2+ ions on iron coordination due to weak positive electric property and small ion radius increased with its initial concentration in the solution. The Langmuir-Freundlich isotherm model among of four selected isotherm models for binary system showed the best fit to the co-coordination reaction between AO- n -PAN and Fe 3+ -Cu 2+ binary solution. Fe-Cu-AO- n -PAN as heterogeneous Fenton catalyst displayed improved catalytic performance than mono-metal complexes due to its better dye adsorption and the synergistic effect between Cu 2+ and Fe 3+ ions during degradation process, and both the alkali-resistant and the reusability of it were improved at the same time.